2018
DOI: 10.29196/jubes.v26i6.1050
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Simulation Outputs for the Mutual Effect of Flow in Weir and Gate System

Abstract: The problem of suspended material and its deposition can be reduced by the combined system of weir and gate flow. Simulating this system aims to understand and analyse the mutual effect of them. Experimental work has been carried out to validate models of the combined system. Vertical sharp edges of gate and weir are tested by changing four times gate opening. The simulations base on RNG k-ε turbulence model and a comparison between flow surface profile and discharge has been done and they showed acceptable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The combined weir-gate system with milder trapezoidal side slopes of bottom opening has a highest efficiency for discharging weir flow Qw which varies between 20% to 40% as compared to the traditional one and this is accepted with (Sarhan and Jalil, 2018) [21], see Fig. (7).…”
Section: Resultsmentioning
confidence: 87%
“…The combined weir-gate system with milder trapezoidal side slopes of bottom opening has a highest efficiency for discharging weir flow Qw which varies between 20% to 40% as compared to the traditional one and this is accepted with (Sarhan and Jalil, 2018) [21], see Fig. (7).…”
Section: Resultsmentioning
confidence: 87%
“…It was observed that there is no significant correlation between the upstream Froude number and the discharge coefficient. Authors in [14] conducted a comparison between the numerical results obtained from the Flow 3D software and experimental tests to investigate the flow characteristics of a compound system comprising a vertical sharp-crested weir and gate. Authors in [15] examined the flow characteristics over a combined sharp-crowned rectangulartriangular weir.…”
Section: Introductionmentioning
confidence: 99%
“…In [13], the numerical results produced by the Flow 3D software were compared with experimental results to examine the flow of a compound system that consisted of a vertical sharp-crowned weir and gate. In [14], the flow characteristics over a combined sharp-crowned rectangular triangular weir were studied.…”
Section: Introductionmentioning
confidence: 99%